Analisis Kepercayaan Konsumen Dalam Memediasi Hubungan Antara Cash On Delivery Dengan Keputusan Pembelian Di Sosial Media Facebook - Fendira lutfianisa; Asep Muhamad Ramdan; Dicky Jhoansyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the effect of trust in mediating the relationship of cash on delivery on purchasing decisions. The research method used is the method of causality. The sample in this study was 347 members of the Facebook Sukabumi Shopping SS Online Buying Forum who had used COD services, which were taken using a simple random sampling technique. Researchers used path analysis data analysis techniques with the help of the AMOS 25 data processing application.The results of this study found that cash on delivery has a significant effect on trust, trust has a significant effect on purchasing decisions and trust is a mediating variable in the relationship between cash on delivery and purchasing decisions. Then trust becomes a bridge in the relationship between cash on delivery and purchasing decisions. Keyword : Cash On Delivery, Facebook, Trust, Purchase Decision